Circular RNA Expression and Regulation Profiling in Testicular Tissues of Immature and Mature Wandong Cattle (Bos taurus) - Khan, Ibrar Muhammad; Liu, Hongyu; Zhuang, Jingyi; Khan, Nazir Muhammad; Zhang, Dandan; Chen, Jingmeng; Xu, Tengteng; Avalos, Lourdes Felicidad Córdova; Zhou, Xinqi; Zhang, Yunhai (Frontiers in Genetics, 2021)
Wandong cattle are an autochthonous Chinese breed used extensively for beef production. The breed tolerates extreme weather conditions and raw feed and are resistant to tick-borne diseases. However, the genetic basis of testis development and sperm production as well as breeding management is not well established in local cattle. Therefore, improving the reproductive efficiency of bulls via genetic selection is crucial, as a single bull can breed thousands of cows through artificial insemination (AI). Testis development and spermatogenesis are regulated by hundreds of genes and transcriptomes. However, circular RNAs (circRNAs) are the key players in many biological developmental processes that have not been methodically described and compared between immature and mature stages in bovine testes. In this study, we performed total RNA-Seq and comprehensively analyzed the circ-RNA expression profiling of the testes samples of six bulls at 3 years and 3 months of developmental age. In total, 17 013 circ-RNAs were identified, of which 681 circRNAs (P-adjust < 0.05) were differentially expressed (DE). Among these DE circ-RNAs, 579 were upregulated and 103 were downregulated in calf and bull testes. The Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses revealed that the identified target genes were classified into three broad functional categories, including biological process, cellular component, and molecular function, and were enriched in the lysine degradation, cell cycle, and cell adhesion molecule pathways. The binding interactions between DE circ-RNAs and micro RNAs (miRNAs) were subsequently constructed using bioinformatics approaches. The source genes ATM, CCNA1, GSK3B, KMT2C, KMT2E, NSD2, SUCLG2, QKI, HOMER1, and SNAP91 were found to be actively associated with bull sexual maturity and spermatogenesis. In addition, a real-time quantitative polymerase chain reaction (RT-qPCR) analysis showed a strong correlation with the sequencing data. Moreover, the developed model of bovine testes in the current study provides a suitable framework for understanding the mechanism of circRNAs in the development of testes and spermatogenesis.